PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA DILIHAT DARI KEBIASAAN MEREKA MENDENGARKAN MUSIK-MUSIK BERBAHASA INGGRIS: PENELITIAN KORELASI - Nurkolip, Dwi (Universitas Nusantara PGRI Kediri, 2019)
In this research, the researcher examined the correlation between student’s habit in listening English music and their vocabulary mastery of the second semester students of the English Department of STKIP PGRI Tulungagung in the academic year of 2018/2019. The purpose of this research was to find out whether or not there is any significant correlation between student’s habit in listening English music and their vocabulary mastery. This research was quantitative research that used correlation method. It was conducted at the English Department of STKIP PGRI Tulungagung. The population was all of the second-semester students of the English Department of STKIP PGRI Tulungagung in the academic year of 2018/2019 that consists of two classes. The total number of the student was 40 students. The sample was 17 students taken by incidental sampling technique. The instruments for collecting data in this research were questionnaire and vocabulary test. The researcher used questionnaire to collect the data of students’ habit in listening English music, while the tests were used to collect the data of students’ vocabulary mastery. In analysing the data, the researcher used Kendall's tau_b in IBM SPSS Statistics 25 program for windows. The result of the research showed that there is a significant relationship between students’ habit in listening English musics and their vocabulary mastery. It can be proved from value sig. (2 tailed) of the Kendall's tau_b test result is 0.010 is smaller than 0.05. Moreover, correlation coefficient value is 0.494, it means there is positive correlation and the level of significant correlation is moderate. Based on the result of the research, it can be concluded that students’ habit in listening English music contributes to their vocabulary mastery.